Do we need to perform bilateral hip bone mineral density examination? - Annisa Layalia Widjanarko (Indonesian Rheumatology Association, 2016)
Background: Bone mineral density (BMD) measurement is one of the method for making osteoporosis diagnosis. World Health Organization (WHO) recommends the measurement of BMD conducted at antero-posterior lumbar vertebrae, unilateral hip (femur), and radius. However, there was a concern about osteoporosis under diagnosis if the measurement is only conducted at unilateral hip. Some studies found significant differences of BMD between both femur and evidence of the importance to examine both femur in making the diagnosis of osteoporosis. This study aims to determine anydifference between right and left femur BMD measurement and to investigate the bone status result with measurement of BMD of bilateral femur in Hasan Sadikin General Hospital. Methods: A retrospective study was conducted from June to November 2015. Patients who received dual-femur BMD testing using General Electrics (GE) Lunar Prodigy dual-energy x-ray absorptiometry at the DXA Facility in Hasan Sadikin General Hospital,Bandung between January 1, 2006 to December 31, 2014 were included. Statistical analysis performed to assess the difference and the correlation between theBMD of two femurs (g/cm2). T-scores of the subject were implemented into bone status according to WHO Diagnostic Criteria for Osteoporosis.Results: From sixty-one patients included in this study, there were difference bone status resulted from BMD of the femoral neck, Ward’s triangle, trochanter, andtotal hip area between right and left femur, although no statistically significance were found. There was a positive correlation between BMD of right and left femurat all areas of femur. There were 16 subjects (26.1%) showed combination level of bone status (normal, osteopenia, or osteoporosis in one femur).Conclusion: BMD results in each area of the right and left femurs are different.Therefore, performing bilateral hip BMD examination as a routine measurement for makingdiagnosis of osteoporosis is important.Keywords: Bone Mineral Density, Dual-energy X-ray Absorptiometry, Femur, Osteoporosis